Does technological progress promote or prevent trade conflict? Evidence from China - Zhao, Qian; Su, Chi-Wei; Dumitrescu Peculea, Adelina (Technological and Economic Development of Economy, 2024)
Using the bootstrap rolling-window subsample Granger causality test from China, this study analyses the influence of technological progress (TP) on trade conflict (TC). The results show that TP can both promote and prevent TC. In 2012 and 2018, TP led to more trade conflicts between China and its trading partners. This result proves the “trade-loss effect”, suggesting that TP in one country promotes TC by threatening other countries’ income. However, TP had a negative influence on TC in 2021 and 2022. This finding is consistent with the “welfare effect”, implying that TP can prevent TC by providing more high-quality and cheaper products for worldwide consumers. This study suggests that the government should adopt appropriate trade policies when encouraging TP to promote bilateral trade. Furthermore, firms should develop their own high-quality irreplaceable products through technological innovation to address TC risk.First published online 22 March 2024